Model of perfect chemical composition of the product according to the requirements of nutriciology - Dorohovich, Antonella; Dorohovich, Victoriya; Petrenko, Nikolay (My University, 2016)
The model of the ideal food. The model is presented in a hierarchical tree, with the distribution of proteins, fats and carbohydrates in chemical composition. The proposed evaluation of food quality control as required, taking into account the weight coefficients
Keywords: nutritsiologiya; herodetic; qualimetry; food; chemical composition; нутріціологія; геродієтика; кваліметрія; харчові продукти; хімічний склад; кафедра технології хлібопекарських і кондитерських виробів